Adaptation of the Practice Environment Scale for military nurses: a psychometric analysis. (21st March 2017) - Swiger, Pauline A.; Raju, Dheeraj; Breckenridge‐Sproat, Sara; Patrician, Patricia A.
Abstract: Aim: The aim of this study was to confirm the psychometric properties of Practice Environment Scale of the Nursing Work Index in a military population. This study also demonstrates association rule analysis, a contemporary exploratory technique. Background: One of the instruments most commonly used to evaluate the nursing practice environment is the Practice Environment Scale of the Nursing Work Index. Although the instrument has been widely used, the reliability, validity and individual item function are not commonly evaluated. Gaps exist with regard to confirmatory evaluation of the subscale factors, individual item analysis and evaluation in the outpatient setting and with non‐registered nursing staff. Design: This was a secondary data analysis of existing survey data. Methods: Multiple psychometric methods were used for this analysis using survey data collected in 2014. First, descriptive analyses were conducted, including exploration using association rules. Next, internal consistency was tested and confirmatory factor analysis was performed to test the factor structure. The specified factor structure did not hold; therefore, exploratory factor analysis was performed. Finally, item analysis was executed using item response theory. The differential item functioning technique allowed the comparison of responses by care setting and nurse type. Results: The results of this study indicate that responses differ between groups and that several individual items could be removed without altering the psychometric properties of the instrument. Conclusion: The instrument functions moderately well in a military population; however, researchers may want to consider nurse type and care setting during analysis to identify any meaningful variation in responses.